Trade like Warren Buffelt - Altucher, James (John Wiley & Sons, 2005)
"Trading is notoriously tough. But Altucher's new book adds a noteworthy addition to the library on Warren Buffett. He shows a lot of Buffett that isn't readily available in the existing common literature. Definitely required reading for any serious Buffett buff." "Finally, someone blows apart the myth that Warren Buffett is a buy-and-hold investor. Altucher has given us an insightful and well-written commentary on how Buffett has amassed his track record, and what we can do to emulate him. He details the trade-by-trade examples. This is a must read for anyone wanting to learn about how the Master Investor works."